A review of the status of e-government implementation in Kenya - Esther Nderitu Imbamba; Nancy Kimile (Regional Journal of Information and Knowledge Management, 2017)
Rationale of Study – Successful implementation of today’s government operations requires effective policy making and system monitoring through relevant data and information. E-government offers an increased portfolio of public services in a cost-effective and efficient manner hence enabling governments to reinvent the ways through which they interact with citizens, private sector, employees and other stakeholders. Consequently, many countries have invested significant resources into collecting, processing, integrating, analysing and reporting data through information and communication technologies (ICTs). The aim of this paper is to review the status of e-government implementation in Kenya.